Persepsi Masyarakat terhadap Dampak Tantangan Teknologi terhadap Hak Asasi Manusia di Indonesia - Judijanto, Loso; Lubis, Arief Fahmi (Sanskara Hukum dan HAM, 2024)
This qualitative research investigates public perceptions of the impact of technological challenges on human rights in Indonesia. Through in-depth interviews with 15 participants from various backgrounds, this research explores the perceived benefits and challenges of technology, attitudes towards government regulation, and trust in technology companies. The findings reveal a nuanced understanding of the intersection of technology and human rights, highlighting concerns about privacy, freedom of expression, and corporate accountability. While technology offers opportunities for empowerment and connectivity, it also carries risks such as data breaches, online censorship and the digital divide. This study underscores the importance of balancing innovation with the protection of fundamental rights and calls for transparent, accountable and ethically responsible practices in the digital realm.